The Influence of Education and Training As Well As Work Experience on The Ability and Performance of Employees of Regional Secretariat of West Papua Province - Yudha Prasetyo; Herningsih Herningsih; Anita Maharani (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: To analyze the effect of education and training and Work Experience on the workability and performance of employees of the Regional Secretariat of West Papua Province Design/methodology/approach: This research was conducted on the staff of the Regional Secretariat of West Papua Province with a population of 278. The sample used was 74 respondents. The determination of the sample was using a purposive sampling technique. The criterions set in the sampling are that the employee has status as a civil servant and has worked for at least 3 years. The independent variables in this study are education and training and work experience. The dependent variable is employee performance, while the intermediate variable is workability. Variable measurements are carried out using a Likert scale. Data analysis was performed using path analysis with the software used was Smart PLS 2. Findings: Equations that could be formed from the results of the analysis were: Z = 0.476X1 + 0.292X2; and Y = 0,345X1 + 0,115X2 + 0,243Z., where Z = ability, Y = performance, X1 = education and training, and X2 = work experience. Education and training had a positive and significant effect on employee workability, indicated by a path coefficient of 0.476 with a T-statistic value of 6.378; Work experience has a significant effect on employee workability, indicated by a path coefficient of 0.292 with a T-statistic value of 3.877; Education and training have a significant influence on employee performance as indicated by a path coefficient of 0.461 with a t-statistic value of 1.958; Work experience has a significant effect on employee performance, indicated by a path coefficient of 0.186 with a T-statistic value of 3.877; Workability has a significant positive effect on employee performance, indicated by a path coefficient of 0.243 with a T-statistic value of 2.427. The advice that can be given is that every employee is always encouraged and allowed to be able to attend education and training. In work placement, the Regional Secretariat of West Papua Province must prioritize work experience so that the resulting performance can be maximized. Research limitations/implications: Number of sample is relative small. Practical implications: State your implication here. Originality/value: This research is original and conducting in West Papua Province. Paper type: Research paper